Autobiography : essays theoretical and critical - Olney, James (Princeton, New Jersey : Princeton University Press, 1980)
Professor Olney gathers together in this book some of the best and most important writings on autobiography produced in the past two decades. Originally published in 1980.
Autobiography and the cultural moment: A thematic, historical and bibliographical introduction / James Olney -- Conditions and limits of autobiography / George Gusdorf -- Full of life now / Barrett J. Mandel -- The Style of autobiography / Jean Starobinski -- Some principles of autobiography / William L. Howarth -- Confessions and autobiography / Stephen Spender -- Recovering literature's lost ground through autobiography / James M. Cox -- Autobiography and the making of America / Robert F. Sayre -- Black autobiography: Life as the death weapon / Roger Rosenblatt -- Malcolm X and the limits of autobiography / Paul John Eakin -- Michel Leiris: Mazemaker / Germaine Brée -- The Other voice: Autobiographies of women writers / Mary G. Mason -- Some versions of memory/ Some versions of bios: The ontology of autobiography / James Olney -- The Veto of the imagination: A theory of autobiography / Louis A. Renza -- Eye for I: Making and unmaking autobiography in film / Elizabeth W. Bruss -- Fictions of the self: The end of autobiography / Michael Sprinker.
Print version record.
Includes bibliographical references (pages 343-352) and index.
Online resource; title from digital title page (JSTOR platform, viewed March 1, 2016).
eBooks on EBSCOhost
Keywords: Autobiography; Autobiographies as Topic; Autobiographie; autobiography (genre); BIOGRAPHY & AUTOBIOGRAPHY -- General; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Autobiography